EFFECT OF VARYING UV IRRADIATION ON GERMINATION AND GROWTH OF COWPEA (Vigna unguiculata (L.) Walp). (FUDMA JOURNAL OF SCIENCES, 2023)
This study was carried out to investigate the effect of different UV exposure time on the germination and early seedling growth of cowpea in order to ascertain the exposure time that affects these developmental stages of plant. The study was laid out in a randomized complete block design of six exposure times including control as treatments with five replicates. Growth parameters of cowpea such as plant height stem girth and number of leaves was determined daily after germination has taken place. All the cowpea seeds in all the treatments exhibited 100% germination at the end of the 9th day. It was observed that the UV irradiation never had any significant negative effect on any of the growth parameters compared with control. This could be due to the short period of exposure or the resistance of the cowpea plant to UV irradiation
Keywords: Cowpea, Growth, Mutation, UV Irradiation